COMPLETELY EDENTULOUS PATIENTS AND ASSOCIATION WITH DIABETES - A RETROSPECTIVE STUDY - David, Debarun; Ganapathy, Dhanraj; Chaudhary, Manjari (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Diabetes mellitus is a disorder in which blood sugar (glucose) levels are abnormally high because the body doesn’t produce enough insulin to meet its needs. Patients with poorly controlled diabetes are at greater risk of dental problems. Classified as type 1 and type 2, the cardinal signs seen are polydipsia, polyphagia, and polyuria. Materials and Method: The data were obtained from the patients who reported to Saveetha Dental College during the time period of June 2019 –March 2020. Records of the patient and their history were obtained. Data of patients with complete dentures were identified, and the history was taken. A total of 40 diabetic complete denture patients were identified, and all the relevant data were extracted and analyzed. The results were analyzed using SPSS software version 2.0 by BM. Result: The data collected from the patient management software were tabulated in SPSS, and descriptive statistics were obtained. Out of the total 40 patients, 24 were male patients and 16 were female patients. In which they were ranging from 45 to 50 years of age. The most common age range for diabetes in completely edentulous patients was seen in 47-50 years of age, with 37.50% prevalence. Male complete denture wearers (60%) were more prevalent to diabetes than females (40%) Conclusion: Our study assessed the prevalence of diabetes in completely edentulous patients; the overall results showed that male edentulous patients were more diabetic and were ranging from the age of 45 years of age to 50 years of age. This study will help to create more awareness regarding diabetes patients who enter the clinic and methods of safe treatment